2-C-Hydroxymethyl-2,3-O-isopropyl-idene-3-C-methyl-beta-L-erythrose - Booth, K; Jenkinson, S; Watkin, D; Fleet, G (2007)
The relative configuration of the title compound, C9H16O5, has been firmly established by X-ray crystallographic analysis. The absolute configuration of this sugar was determined by the use of 2-C-methyl-d-ribono-1,4-lactone as the starting material. The structure exists as a hydrogen-bonded network, with each mol-ecule being a donor and an acceptor for two hydrogen bonds. © International Union of Crystallography 2007.